ION MICROPROBE STUDIES OF EFREMOVKA CAIS: I. MAGNESIUM ISOTOPE COMPOSITION - Goswami J.N.; Srinivasan G.; Ulyanov A.A. (My University, 1994)
Five coarse-grained Ca-Al-rich refractory inclusions (CAIs) from the Efremovka CV3 chondrite are analysed for their magnesium isotopic composition using an ion microprobe. The analysed inclusions represent the three common CAI types (A, B1, and B2). Data for magnesium isotopic composition of the major mineral phases (melilite, spinel, fassaite, and anorthite) in these inclusions are used to determine intrinsic magnesium isotopic fractionations and to identify nonlinear effect in 26Mg due to the decay of extinct 26Al. The magnesium isotopic mass fractionation, F(Mg), generally favours the heavier isotopes, as is expected in the case of coarse-grained CAIs. The F(Mg) data for two of the inclusions, however, show contrasting trends. Sympathetic behaviour found in both isotopic and petrographic data in one type B1 inclusion suggests that the parent melt of this inclusion experienced a short-duration volatilization event prior to crystallization. The isotopic data also suggest possible presence of relict spinel in this inclusion that constrains the cooling rate of the parent melt to >70°C/h during crystallization. Hot and dense nebular settings that allow for such fast cooling can only be localized in nature.The pristine nature of the Efremovka CAIs, as evident from the lack of secondary alteration products in them, is well supported by the isotopic data. Three of the five inclusions yield well-behaved Mg-Al isochrons with ()0 close to the canonical value of 5 × 10−5. The anorthite data for another inclusion suggest minor disturbance in the isotopic systematics and yield a nearly well-behaved isochron with a slightly lower value of ()0. Data for melilite and anorthite in the fifth inclusion define apparent isochrons that suggest partial re-equilibration and exchange of magnesium isotopes between these two phases. The Efremovka data are suggestive of a relatively homogeneous distribution of 26Al in the solar nebula.